Applying an Individualized Instruction Plan (IIP) to Enhance Cognitive Skills in Recognizing Numbers 1-9 for Children with Autism at the Preparatory Level, Lamphun Special Education Center - จี้รัตน์, นางสาวธิญดา; โพธาสินธุ์, วารุณี; สุขยศศรี, ศรีทัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This education aimed to develop an Individual Implementation Plan (IIP) using educational games to enhance cognitive skills in recognizing and understanding numbers 1-9 among children with autism at the preparatory level at the Lamphun Special Education Center. The target group consisted of two girls aged 4 and 5, diagnosed with autism, selected through purposive sampling. The study employed a one-group pretest-posttest design.Research instruments included six personalized instructional plans designed by the researcher and validated by three experts, along with behavioral observation checklists administered before and after the intervention. The results showed that all six educational game-based IIP plans were rated as highly appropriate by the experts. Furthermore, the use of these games significantly improved the cognitive skills related to number recognition and understanding among the participants, advancing from a “very low” to a “high” level according to the established criteria.The findings indicate that educational games are effective tools for promoting cognitive development in children with autism. These instructional strategies can serve as a model for personalized learning approaches, especially for children with special needs at the early childhood level, supporting long-term development in a meaningful and engaging manner.